“I Was Never So Unmanned Before”: (Emasculating) Imperialism and the Late Victorian Crisis of Masculinity in Fin-de-Siècle Fiction - Martín-González, Juan José (My University, 2015)
The Victorian Fin de Siècle was a period characterized by decay, anxiety and identity fragmentation. Within the convolution of race, gender and class which was evinced in those decades, the crisis of masculinity outstands as being closely tied with the state of the British Empire in the late Victorian Era. This paper aims at scrutinizing a series of underread lateVictorian texts, namely Richard Marsh’s The Beetle (1897) and a selection of Arthur Conan Doyle’s non-Sherlockian short fiction, to exhibit the intimate relationship between colonial tropes and (fe)male characters in late-Victorian popular culture. In particular, the contact or confrontation with the Oriental Other and the negotiation with a violent colonial past are appropriated to raise alarms over the perceived emasculation of British males and the weakening of ‘Anglo-Saxon’ manhood. In more general terms, the texts under analysis in this paper epitomize fin-de-siècle doubts over whether British men were fit enough to deal with the arduous task of keeping an ever-growing empire and specifically to confront the Oriental other, which is quite telling at a time when gender roles were increasingly shaded.
Keywords: Novela inglesa - S. XIX - Crítica e interpretación; Victorian; Fin-de-siècle; Masculinity